The Influence of Placement and Competency on Motivation and Its Implications for the Performance of Bhayangkara Hospital Jambi Employees - Rahma Agustina; M. Zahari; Osrita Hapsara (Dinasti Publisher, 2024)
This research aims to find out and analyzeThe influence of placement and competency on motivation and its implications for the performance of Bhayangkara Hospital Jambi employees. This type of research uses descriptive and verification research. The object of this research is the 93 employees of Bhayangkara Hospital Jambi. This research uses the path analysis method (Path Analysis). Based on the results of the questionnaire regarding the placement of the score, it is 10,872 which is included in the